Dios, Patria y Democracia: el ideario de la Fuerza Democrática Nicaragüense (FDN) en El Libro Azul y Blanco de 1983 - Rueda-Estrada, Verónica; Vázquez Medeles, Juan Carlos (CIICLA, Universidad de Costa Rica, 2023)
On September 1983 the command of the Nicaraguan Democratic Force (FDN) finished writing The Blue and White Book (LAyB). Two thousand copies were printed in Honduras under the editorial seal of the FDN Communications Center, and in 1984 were given to members of the armed organization who would enter Nicaragua from Honduras. It was a code of conduct and an ideological manual that sought to prepare the combatants to deal with the villagers and to take advantage of these opportunities to explain their struggle and recruit them. On 2001 the document was declassified from the National Security Archives (NSA). The objective of this article is to analyze the ideology of the FDN through the LAyB with the purpose of determining the causes of the counterrevolutionary uprising, to understand the strategies planned to add armed followers to the Contra and the logic behind their struggle, for which other counterrevolutionary documents produced at the time are also used.